Evaluating the long-term aesthetic outcomes of a customized nanofibrous temporary epidermal matrix in facial burn treatment - Alexandra Schulz; Carmo Kanho; Paul Christian Fuchs; Wolfram Heitzmann; Jennifer Lynn Schiefer (Elsevier, 2024)
Introduction: Facial burn injuries have a profound impact on patients' lives due to the significant alterations in physical appearance. Recent advancements in medical technology aim to improve the healing process while minimizing scar formation. This study investigates the clinical outcomes of treating superficial to partial-thickness facial burns with a nanofibrous temporary epidermal matrix over a 12-month period, encompassing objective and subjective scar assessments. Methods: A prospective cohort analysis was conducted involving ten patients with facial burns. The study assessed re-epithelialization time, complications, and long-term objective scar outcomes at the 8-month and 12-month marks. Results: The study revealed a notable mean re-epithelialization time of 12.1 days (Standard Deviation: 3.78) without any complications. At the 8-month assessment, there were no discernible differences in objective scar outcomes between treated and intact areas. After a 12-month follow-up, a subtle reduction in skin quality was observed, which lacked clinical significance. Conclusion: These findings emphasize the potential of nanofibrous temporary epidermal matrices as patient-friendly dressings for managing second-degree to partial-thickness facial burns. Their ability to address facial burns without increasing patient discomfort suggests the potential for a less traumatic healing experience, ultimately enhancing overall patient recovery.